iChase: Supporting Exploration and Awareness of Editing Activities on Wikipedia - Henry Riche, Nathalie; Lee, Bongshin; Chevalier, Fanny (In Proceedings of AVI 2010, 2010)
To increase its credibility and preserve the trust of its readers, Wikipedia needs to ensure a good quality of its articles. To that end, it is critical for Wikipedia administrators to be aware of contributors‘ editing activity to monitor vandalism, encourage reliable contributors to work on specific articles, or find mentors for new contributors. In this paper, we present iChase, a novel interactive visualization tool to provide administrators with better awareness of editing activities on Wikipedia. Unlike the currently used visualizations that provide only page-centric information, iChase visualizes the trend of activities for two entity types, articles and contributors. iChase is based on two heatmaps (one for each entity type) synchronized to one timeline. It allows users to interactively explore the history of changes by drilling down into specific articles and contributors, or time points to access the details of the changes. We also present a case study to illustrate how iChase can be used to monitor editing activities of Wikipedia authors, as well as a usability study. We conclude by discussing the strengths and weaknesses of iChase.